Diagnostic, Therapeutic and Prognostic Implications of Urothelial Carcinoma, A Review: Implications of Urothelial Carcinoma - Shahzad, Muhammad; Nasir Jamil, Muhammad; Ashraf, Hamza; Ul Islam, Ehsan (Pakistan Journal of Health Sciences, 2023)
Urothelial carcinomas are cancerous tumors that can affect both the lower and upper urinary system and develop from the urothelial epithelium. The majority of urinary tract cancers (90–95%) are bladder tumors. UTUCs are rare, making up just 5–10% of UCs and their annual prevalence in Western nations is thought to be close to two instances per 100,000 people. This review of the article gives a general overview of the introduction, classification, diagnostic and therapeutic importance of urothelial carcinoma. About 48 recent publications, suitable for literature review, were retrieved from three different databases: PubMed, Sci. hub, and Google scholar. Careful reading and analysis of the literature review was carried out using inclusion and exclusion criteria. Despite significant improvements in prognosis and treatment, such as surgical methods, different adjuvant therapies, radical cystectomy, and robot-assisted radical cystectomy, tumors still recur with a dismal 5-year survival rate, making the addition of novel target-based therapies necessary to improve the overall outcome. Future treatments targeting genomic changes and the immune system should be tailored to each person’s molecular profile. The majority of cases of urothelial carcinoma have been linked to numerous risk factors. For individuals with metastatic urothelial cancer, which includes bladder cancer and cancers of the upper urinary tract and urethra, numerous therapy options have been made available recently. These include targeted therapies and immunotherapy. This review recommended the possible way for diagnostic, therapeutic and prognostic implications of urothelial carcinoma.